Digital copyright : law and practice - Stokes, Simon, 1963- (Oxford : Hart Publishing, 2014)
Now in its fourth edition, this text has been updated and revised to take account of legal and policy developments in copyright law and related areas, in particular the increasing role of the European Court of Justice in shaping EU copyright law.
Why digital copyright matters -- Digital copyright : the basics -- Digital database law and the internet -- Digital moral rights : the basics -- Digital rights and competition law -- Software copyright -- Digital copyright and e-commerce -- Digital copyright, web 2.0, e-publishing and apps -- Protecting and managing your digital copyright assets.
Includes bibliographical references and index.
Keywords: Copyright -- Computer files -- United Kingdom; Copyright -- Computer files -- European Union countries; Copyright -- Computer files; Copyright and electronic data processing -- United Kingdom; Copyright and electronic data processing -- European Union countries; Copyright and electronic data processing; Copyright, International